2020
DOI: 10.3390/ph13040071
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Antidiabetic Activities of Leaves and Stems of Uapaca bojeri Bail. (EUPHORBIACEAE), an Endemic Plant of Madagascar

Abstract: Uapaca bojeri is an endemic Malagasy plant used by the local population. This work aimed to evaluate antioxidant, anti-inflammatory, and antidiabetic activities of the methanol extracts of U. bojeri leaves and stems and to report their total phenolic content and the bioactive compound content by HPLC methods. Antioxidant capacity was determined by DPPH and ferric reducing antioxidant power (FRAP) assays. An in vivo carrageenan-induced paw oedema and acetic acid-induced writhing test in mice were used for anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Cinnamic acids (such as caffeic acid) can inhibit or reduce thrombotic tendency, as reported in several studies [46,48]. Ellagic acid was the most abundant molecule in the class of benzoic acids (Table 6), in particular in A. theiformis (C2) and C. verum (C12) with mean values of 324.60 ± 2.32 mg/ 100 g DW and 325.01 ± 2.27 mg/100 g DW, respectively, while gallic acid showed lower amounts (<10 mg/100 g DW).…”
Section: Phytochemical Composition Of the Individual Plants That Constitute The Comorian Teamentioning
confidence: 68%
See 1 more Smart Citation
“…Cinnamic acids (such as caffeic acid) can inhibit or reduce thrombotic tendency, as reported in several studies [46,48]. Ellagic acid was the most abundant molecule in the class of benzoic acids (Table 6), in particular in A. theiformis (C2) and C. verum (C12) with mean values of 324.60 ± 2.32 mg/ 100 g DW and 325.01 ± 2.27 mg/100 g DW, respectively, while gallic acid showed lower amounts (<10 mg/100 g DW).…”
Section: Phytochemical Composition Of the Individual Plants That Constitute The Comorian Teamentioning
confidence: 68%
“…Flavonols show important health-promoting properties in humans because they may inhibit in vitro oxidation of low-density lipoproteins and cyclooxygenase and modulate the metabolism of arachidonic acid. Moreover, they may attenuate inflammation and quench active oxygen species inhibit [45,46].…”
Section: Phytochemical Composition Of the Individual Plants That Constitute The Comorian Teamentioning
confidence: 99%
“…It implies that there is not only ovatodiolide but also other phytochemicals could effect on HeLa cancer cell and/or zebrafish embryos. Although the obtained results from this study demonstrated that the AI-EtE has possible use in traditional medicine against cervical cancer, in the future studies, chemical compositions of AI-EtE should be addressed by using HPLC and/or HPTLC methods [ 51 , 52 ] to identify the phytochemicals that are able to be used as fingerprints for quality control of the AI-EtE.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenolic compounds may be divided into many several classes [58]; cinnamic acid, benzoic acids, catechins, and flavonols are the most abundant in foods [59,60]. Low quantities of polyphenols are usually observed in complex plant systems and it is very difficult to isolate them in high amounts [61,62].…”
Section: Phenolic Compoundsmentioning
confidence: 99%